Skyline Queries in SPARQL: An Overview - Goncalves Da Silva, Marlene; Aguilera Faraco, Ana Isabel (Rev. Téc. Fac. Ing. Univ. Zulia, 2022)
The growth of RDF (Resource Description Framework) datasets and the expansion of their use in conjunction with the definition of SPARQL, a declarative query language, have made RDF data management an active area of research and development. In this regard, mechanisms have been proposed to help users find their desired answers in less time, including ranking methods and preference-based queries. Skyline queries constitute one of the most practical and predominant types of preference-based queries. The aim of this work was to provide a guide to specifying SPARQL skyline queries using syntax proposed in state-of-the-art works, and SPARQL versions 1.0 and 1.1. The results show the possibility of rewriting skyline queries in SPARQL to express preferences. We plan to develop a tool to translate SPARQL skyline queries applying the different grammars proposed, into SPARQL 1.0 and 1.1 with the aim of providing an automatic mechanism of translation.